Epigenetic Regulation of BDNF Gene during Development and Diseases - Chen, Kuan-Wei (Int J Mol Sci, 2017)
Brain-derived neurotrophic factor (BDNF) is required for the development of the nervous system, proper cognitive function and memory formation. While aberrant expression of BDNF has been implicated in neurological disorders, the transcriptional regulation of BDNF remains to be elucidated. In response to different stimuli, BDNF expression can be initiated from different promoters. Several studies have suggested that the expression of BDNF is regulated by promoter methylation. An emerging theme points to the possibility that histone modifications at the BDNF promoters may link to the neurological pathology. Thus, understanding the epigenetic regulation at the BDNF promoters will shed light on future therapies for neurological disorders. The present review summarizes the current knowledge of histone modifications of the BDNF gene in neuronal diseases, as well as the developmental regulation of the BDNF gene based on data from the Encyclopedia of DNA Elements (ENCODE).